The Coactivator PGC-1 Cooperates with Peroxisome Proliferator-Activated Receptor α in Transcriptional Control of Nuclear Genes Encoding Mitochondrial Fatty Acid Oxidation Enzymes - Vega, Rick B. (American Society for Microbiology, 2000)
Peroxisome proliferator-activated receptor α (PPARα) plays a key role in the transcriptional control of genes encoding mitochondrial fatty acid β-oxidation (FAO) enzymes. In this study we sought to determine whether the recently identified PPAR gamma coactivator 1 (PGC-1) is capable of coactivating PPARα in the transcriptional control of genes encoding FAO enzymes. Mammalian cell cotransfection experiments demonstrated that PGC-1 enhanced PPARα-mediated transcriptional activation of reporter plasmids containing PPARα target elements. PGC-1 also enhanced the transactivation activity of a PPARα-Gal4 DNA binding domain fusion protein. Retroviral vector-mediated expression studies performed in 3T3-L1 cells demonstrated that PPARα and PGC-1 cooperatively induced the expression of PPARα target genes and increased cellular palmitate oxidation rates. Glutathione S-transferase “pulldown” studies revealed that in contrast to the previously reported ligand-independent interaction with PPARγ, PGC-1 binds PPARα in a ligand-influenced manner. Protein-protein interaction studies and mammalian cell hybrid experiments demonstrated that the PGC-1–PPARα interaction involves an LXXLL domain in PGC-1 and the PPARα AF2 region, consistent with the observed ligand influence. Last, the PGC-1 transactivation domain was mapped to within the NH(2)-terminal 120 amino acids of the PGC-1 molecule, a region distinct from the PPARα interacting domains. These results identify PGC-1 as a coactivator of PPARα in the transcriptional control of mitochondrial FAO capacity, define separable PPARα interaction and transactivation domains within the PGC-1 molecule, and demonstrate that certain features of the PPARα–PGC-1 interaction are distinct from that of PPARγ–PGC-1.